The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/car.2646
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences among Commercially Sexually Exploited Youth in Israel

Abstract: Research on commercial sexual exploitation (COMSE) of youth tends to focus on young females as victims, and much less is known about male and transgender commercially sexually exploited youth (COMSEY). Understanding the psychosocial background and past COMSE experiences among COMSEY is important to provide support for gender‐specific or gender‐inclusive interventions for COMSEY. The study included 57 cisgender females, 40 males and 23 transgender females who received services from a multi‐module programme for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…They found quite strong gendered differences in how these two groups were perceived and how professionals worked with them, but very similar experiences in terms of their exposure to prior abuse and domestic violence. These findings would seem to concur with those of Shilo et al (2021) who recognise the unique vulnerability and risk factors for individual young people, regardless of their gender identity. They call for interventions with sexually exploited young people to 'be tailored to reflect various needs specific to gender identity, sexual orientation, race and religion, as well as to the lived individual experiences of the youth' arguing for gender-inclusive rather than gender-specific programmes (Shilo et al, 2021, p. 43).…”
Section: Promoting Gender-inclusive Interventions For Young People Whsupporting
confidence: 83%
See 1 more Smart Citation
“…They found quite strong gendered differences in how these two groups were perceived and how professionals worked with them, but very similar experiences in terms of their exposure to prior abuse and domestic violence. These findings would seem to concur with those of Shilo et al (2021) who recognise the unique vulnerability and risk factors for individual young people, regardless of their gender identity. They call for interventions with sexually exploited young people to 'be tailored to reflect various needs specific to gender identity, sexual orientation, race and religion, as well as to the lived individual experiences of the youth' arguing for gender-inclusive rather than gender-specific programmes (Shilo et al, 2021, p. 43).…”
Section: Promoting Gender-inclusive Interventions For Young People Whsupporting
confidence: 83%
“…Although Shilo et al (2021) found some gender differences in the young people's psychosocial background factors, they did not find any solid gendered profiles. They conclude that these youth 'cannot be characterised solely or predominantly by their gender identity' (Shilo et al, 2021, p. 43), but that their findings 'support the recommendation to use an intersectional lens… rather than a gendered one…, taking into consideration gender identity, race and sexual orientation as vulnerability variables to understand the paths of youth to commercial sexual exploitation and the ways to help them' (Shilo et al, 2021, p. 43).…”
Section: Promoting Gender-inclusive Interventions For Young People Whmentioning
confidence: 73%
“…Several studies have identified risks for experiencing CST in the U.S., including child maltreatment (e.g., prior sexual abuse), involvement in foster care, a history of running away, alcohol and substance use/abuse, poor mental health, justice system involvement, unstable home environments, peer or family influence (e.g., witnessing others engage in sex work), identifying as part of the LGBTQ + community, severe physical disabilities, and/or low cognitive abilities [ 8 , 16 •, 17 , 19 , 21 25 ]. Similar risk factors have also been reported in Canada and Israel [e.g., 21 , 26 ]. Research comparing domestic and international trafficking suggests that risk factors may differ depending on the context.…”
Section: Risk Factorssupporting
confidence: 82%